THE INFLUENCE OF THE INTERPRETATION OF QUR AN AN-NAHL VERSE 91 AND HISTORY OF PROPHET LEADERSHIP RELATED TO THE TRUST OF LEADERS WITH MEN AND WOMEN IN PERSPECTIVE CHOOSING ELECTIONS IN THE TANJUNG DISTRICT EAST JAVA - Muhammad Niamulloh; Abdul Muhid (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2020)
Islamic religion with the most adherents in Indonesia. As a religion, Islam always answers and suits the needs of the times. How Islam is a religion that regulates the whole concept of humanity in goodness. In a more privacy-based scope of benefit, namely the election of leaders, is also governed by Islam. In the concept of leadership, Islam also explains in the Qur'an and the Hadith by narrating the history of the prophets when leading their people, or other figures such as the king of Zulkwarna or others. It should be underlined, it can be seen that implicitly, Islam appoints men to lead, this is a tradition later on and until now. This is the question, how does Islam appoint men to be leaders? Is it because of trust. In this discourse, the writer deliberately seeks to know whether this tradition is realized by the community, or only sees from another paradigm. This background is applied through research in TanjungJabung Timur, Jambi Province. In order to measure how much the enthusiasm of this tradition is applied or abandoned by the community.